Leśmianowska ballada o niedoskonałości = Leśmian's ballad on imperfection - Kokoszka, Magdalena (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
It seems that Bolesław Leśmian could anticipate the contemporary critical reflection on disability (disability studies). According to Tymoteusz Karpowicz, the poetry of the author of "The Beggar's Ballad" ["Ballada dziadowska"] can be read, among other things, as a defence of being what you are and not necessarily what you want to be. This thesis is intended to serve as a starting point to look more closely at some of Leśmian's characters as well as his concept of the community, which was marked by imperfections.
Keywords: Leśmian, Bolesław (1877-1937); Swinarski, Artur Maria (1900-1965); "Ballada dziadowska"; wspólnota; niepełnosprawność; "The Beggar's Ballad"; community; disability